2022
DOI: 10.17512/jamcm.2022.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of two-dimensional Fredholm integro-differential equations by Chebyshev integral operational matrix method

Abstract: This paper presents the Chebyshev Integral Operational Matrix Method (CIOMM) for the numerical solution of two-dimensional Fredholm Integro-Differential Equations (2D-FIDEs). The process of the method is obtaining the operational matrix of integration by evaluating a 2D integral of 2D Chebyshev polynomial basis functions and assuming approximate solutions of the 2D-FIDEs as a truncated 2D Chebyshev series. This leads to a system of linear algebraic equations which are solved to obtain the values of the unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These include fractional order derivatives [7,27]. The mathematical model equations can also be discretized using other base polynomials such as ones based upon Chebyshev polynomials or integrals [1,21]. Recently, HBV has been the important focus of authors and researchers to capture the Caputo type fractional operator [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…These include fractional order derivatives [7,27]. The mathematical model equations can also be discretized using other base polynomials such as ones based upon Chebyshev polynomials or integrals [1,21]. Recently, HBV has been the important focus of authors and researchers to capture the Caputo type fractional operator [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with different approch for solving integro-diffrential equations can be found in [17][18][19][20][21][22] In this work, Akbari-Ganji's Method (AGM) is proposed for the solution of Volterra Integro-Differential Difference Equations (VIDDE). The approach of [14] is followed.…”
Section: Introductionmentioning
confidence: 99%